Dissecting charge relaxation pathways in CdSe/CdS nanocrystals using femtosecond two-dimensional electronic spectroscopy. Issue 13 (21st March 2017) - Jarrett, J. W.; Yi, C.; Stoll, T.; Rehault, J.; Oriana, A.; Branchi, F.; Cerullo, G.; Knappenberger, K. L.
Abstract : Exciton relaxation dynamics of CdSe and quasi-type-II CdSe/CdS core/shell nanocrystals were examined using femtosecond two-dimensional electronic spectroscopy (2DES). Abstract : Exciton relaxation dynamics of CdSe and quasi-type-II CdSe/CdS core/shell nanocrystals were examined using femtosecond two-dimensional electronic spectroscopy (2DES). The use of 2DES allowed for determination of structure-specific and state-resolved carrier dynamics for CdSe nanocrystals formed with five, or fewer, CdS passivation monolayers (ML). For CdSe and CdSe/CdS nanocrystals formed with one through three MLs of CdS, excitation using broad bandwidth femtosecond visible laser pulses generated electron–hole pairs among the | X 1 〉 = 2.14 eV and | X 2 〉 = 2.27 eV exciton states. For both excitations, the electron is promoted to the lowest energy excited (1Se ) conduction-band state and the hole is in the 1S3/2 ( X 1 ) or 2S3/2 ( X 2 ) valence-band state. Therefore, the relaxation dynamics of the hot hole were isolated by monitoring the-time-dependent amplitude of 2DES cross peaks. The time constant for hot hole relaxation within the CdSe valence band was 150 ± 45 fs. Upon passivation by CdS, this hole relaxation time constant increased to 170 ± 30 fs (CdSe/CdS-3ML). This small increase was attributed to the formation of a graded, or alloyed, interfacial region that precedes the growth of a uniform CdS capping layer. The small increase in hole relaxation time reflects the larger nanocrystal volume of the CdSe/CdS system with respect to the CdSe nanocrystal core. In contrast, the dynamics of larger core/shell nanocrystals (≥4ML CdS) exhibited a picosecond buildup in 2DES cross-peak amplitude. This time-dependent response was attributed to interfacial hole transfer from CdS to CdSe valence-band states. Importantly, the 2DES data distinguish CdSe exciton relaxation from interfacial carrier transfer dynamics. In combination, isolation of structurally well-defined nanocrystals and state-resolved 2DES can be used to examine directly the influence of nanoscale structural modifications on electronic carrier dynamics, which are critical for developing nanocluster-based photonic devices.